(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: rheumatic disorder; spectrum; teaching hospital DOI: 10.3329/jcmcta.v20i1.4927 Journal of Chittagong Medical College Teachers’ Association 2009: 20(1):6-11